The effect of land use density, diversity and pedestrian infrastructure design to rail transit ridership in Kuala Lumpur, Malaysia - Jaafar Sidek, Mohd Farid; Mohamad Zulkifli, Siti Nur Awani; Nik Othman, Nik Nurul 'Aziemah; Kadar Hamsa, Abdul Azeez; Mohd Noor, Norzailawati; Ibrahim, Mansor (Universiti Tunku Abdul Rahman (UTAR), 2016)
The investment in road infrastructure cannot outpace the growing travel demand in Kuala Lumpur. Thus, public transit is the best solution to reduce road congestion and provision of new road infrastructure. This paper is to analyse the effect of land use density, diversity and pedestrian infrastructure design to rail transit ridership in Kuala Lumpur. There are three rail transit stations are selected along the same transit line to examine in terms of the number of passenger ridership and its relationship with land use Density, Diversity and pedestrian infrastructure Design (3Ds). The data is collected with land use map to examine the multiple land uses around each transit station. It is also to examine the land use diversity level surrounding each transit station. The pedestrian infrastructure survey is to determine the accessibility level to transit station. Data analysis is carry out by analytical tools of statistical analysis. The finding is effect of 3Ds to the passenger ridership of three selected transit stations within one-kilometer radius. The passenger ridership characteristics in terms of 3Ds will benefit the future selection of propose transit station.